Efficacy and safety of Lemborexant in treating adult patients with insomnia in China: a single-center, retrospective observational study - Jian, Weiying; Feng, Minyan; Zhao, Yifan; Li, Jin (Frontiers in Neurology, 2025)
BackgroundExcept for one case report, there has been no published study of Lemborexant treatment for patients with insomnia in China. This study investigated efficacy and safety of Lemborexant in treating Chinese patients with insomnia.MethodsIn this single-center, retrospective observational study, adult patients diagnosed with insomnia with an Insomnia Severity Index (ISI) score of ≥8 who were prescribed Lemborexant at Guangzhou United Family Hospital from January 2023 to July 2024 and who had ≥2 follow-up ISI assessment(s) were included. The primary outcome was change in the ISI total score from baseline after 4 weeks of Lemborexant treatment. Treatment-emergent adverse events (TEAEs) were collected.ResultsForty patients with a mean baseline ISI score of 17.0 ± 3.3 were included. The treatment continuation rate during the median 8-week (range: 2–20) follow-up was 90%. The ISI total score was reduced significantly from baseline after 4 weeks of treatment (−10.2 ± 3.0, p < 0.001), and was further reduced after 8 weeks of treatment (−12.7 ± 3.7, p < 0.001). Significant improvement in ISI total score at week 8 over week 4 was also observed. Both the Patient Health Questionnaire-9 and the General Anxiety Disorder-7 scores improved significantly after 4 weeks and 8 weeks of treatment. Thirty five (87.5%) patients were Lemborexant responders (ISI < 8). Age, combination therapy and Lemborexant 10 mg qn were independent factors associated with Lemborexant responders. One (2.5%) patient experienced mild dizziness. No patient discontinued the treatment due to TEAE(s).ConclusionLemborexant treatment was effective and safe in treating a wide variety of Chinese patients with different symptom(s) of insomnia.